Análise pedológica em topossequência através da relação entre precipitação e a perda de sedimentos na encosta Itagiba, zona norte de Santa Maria - RS - Marques, Rodrigo Diniz (2010)
The occupancy in risk areas in Brazilian cities occurs mainly due to the processes of social inequality, bad management and absence of public planning. In Santa Maria, Rio Grande do Sul, it is not different, and there is a large number of occupancy in risk areas, being one of these areas the Itagiba hillside, located at Chácara das Flores quarter, in the north side of the city. The scheme of the railway Santa Maria Uruguaiana, developed by the Belgian partnership in 1890, modified the north hogback of Vila Kennedy, changing the configuration of the landscape and altering the erosive processes in this area. This alteration occurred mainly in the topography of the land, represented by the declivity and by the length of inclination on two distinct geological formations: the Santa Maria Formation Alemoa Member of silty clay constitution in the east part of the hillside, and the Caturrita Formation of cemented sandy constitution in its west portion. The main objective of this work was to contribute to the understanding of the erosive processes in hillsides, establishing a relation between precipitation and total sediment loss as well as the characteristics of the soil profile that may be contributing for the evolution of the relief in the area where Itagiba hillside is located. It was also aimed at establishing the relation and the correlation of the sediment loss of pedological volume in ditch 2 and the meteoric precipitation, the sediment loss through granulometric fraction in ditch 2, the infiltration coefficient in pedological volumes in ditches 1, 2 and 3, the consistency limits of pedological volumes in ditches 1, 2 and 3; delineating a topossequence on the hillside and settling three ditches and five tradages in order to analyze the pedological volumes; understanding the process of anthropic occupancy and the erosive processes in the Itagiba hillside environment; and ,lastly, understanding the landscape configuration under the perspective of surface and subsurface erosive processes thus providing information for the urban planning of the area. The results showed that there is a positive correlation between sediment loss and meteoric precipitation at any season of the year, being the higher losses in silt and clay fractions. The granulometric analysis showed that sand fraction decreases at the highest point of ditches 1, 2 and 3 in direction to the basis, and silt and clay fractions increase in the same direction thus reducing the infiltration coefficient which in volume 3 of the three ditches becomes impermeable enhancing the horizontal flows (hortonian flow), accelerating the erosive processes at the hillside and contributing for the differentiated configuration of the landscape of Itagiba hillside.